The weighted diaphony - Dimitrievska Ristovska, Vesna; Grozdanov, Vassil (My University, 2006)
In the present paper the authors introduce a new quantitative measure for uniform distribution of sequences in [0, 1)s , the so-called “weighted diaphony.” The definition of the weighted diaphony is based on using the trigonometric functional system. At a special choice of the parameters α and γ on which the weighted diaphony depends, the “classical” diaphony introduced by Zinterhof is obtained. It is shown that the computing complexity of the weighted diaphony of an arbitrary net composed of N points in [0, 1)s is O(S.N2 ). Relationship between the worst-case error of the quasi-Monte Carlo integration in a class of weighted Hilbert space and the weighted diaphony is obtained.
Keywords: weighted diaphony, diaphony, worst-case error